2021
DOI: 10.1103/physrevphyseducres.17.020134
|View full text |Cite
|
Sign up to set email alerts
|

Informal physics programs as communities of practice: How can programs support university students’ identities?

Abstract: Many undergraduate and graduate physics students participate in some form of public engagement throughout the course of their studies, often through groups supported by physics departments and universities. These informal teaching and learning programs can offer unique opportunities for physics identity development. Understanding how physics identities can be fostered will allow us to work toward a field that is inclusive of more identities. In this study, we build on previous work to investigate studentfacili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…This helped develop their physics identity, their feeling of belonging to the physics community, and their career skills. Another study [37] identified interactions with the audience, working in teams, thorough training, clear mission, and supportive schedule as key structures in ISEAs that help build the physics identity of undergraduate participants.…”
Section: Improving Mentoring Teaching and Trainingmentioning
confidence: 99%
See 2 more Smart Citations
“…This helped develop their physics identity, their feeling of belonging to the physics community, and their career skills. Another study [37] identified interactions with the audience, working in teams, thorough training, clear mission, and supportive schedule as key structures in ISEAs that help build the physics identity of undergraduate participants.…”
Section: Improving Mentoring Teaching and Trainingmentioning
confidence: 99%
“…Furthermore, there is research within the Physics Education Research (PER) field that have looked at the positive impact that facilitating ISEAs has on the students who organize them, including fostering physics identity, development of communication and pedagogical skills, sense of belonging, and confidence among peers [7,25,36,37,[48][49][50][51][52][53].…”
Section: Recruiting and Equity/diversity/inclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, the informal physics education research (IPER) community has investigated the development and impact of informal physics programs on their participants and facilitators [1][2][3]. For example, researchers have shown that different structures within informal physics support physics identity development [4][5][6]. In particular, informal physics programs are spaces for an increased sense of belonging to the physics community, and for gaining confidence and communication skills necessary for one's career [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…One place where a physics identity can develop are informal learning spaces that allow for participants to become agents of their own learning [3]. Prior work has shown that some informal physics programs can support physics identities of its members by serving as communities of practice [4][5][6][7][8][9]. However, this prior work is focused on established informal physics programs, i.e.…”
Section: Introductionmentioning
confidence: 99%